Evaluation of the Effects of Urtica Dioica L. Supplementation on Egg Quality and Blood Parameters in Laying Hens - Svetlana Grigorova; Natasha Gjorgovska; Evgeni Petkov; Vesna Levkov (Veterinarija ir Zootechnika, 2022)
The purpose of the current research was to study the influence of dietary supplementation of nettle (Urtica dioica) on laying performance, egg quality and blood serum biochemical parameters of layers. A total of 60 laying hens (42 weeks old) from Lohman Klassik Brown breed were randomly allocated into three groups: a control and two experimental groups (n = 20 hens per group). All layers received compound feed with the following nutritional value: 2710 Kcal/kg metabolizable energy; 16.44% crude protein; 3.32% crude fats; 4.58% crude fibres; 3.73% Са; 0.49% Р. The hens from the experimental groups received 0.3% (experimental group 1) and 0.5% (experimental group 2) of dried nettle with the diet. Both experimental groups had significantly higher egg yolk pigmentation (p < 0.001) compared with the control group. A significantly lower egg yolk cholesterol content was found in hens from experimental group 1 (p < 0.05). Nettle addition reduced significantly blood serum glucose (p < 0.01 and p < 0.05 in experimental groups 1 and 1, respectively) as well as the total serum cholesterol content (p < 0.001).
Keywords: Urtica dioica, layers, egg quality, biochemical parameters